The Incomplete Tyranny of Dynamic Stimuli: Gaze Similarity Predicts Response Similarity in Screen‐Captured Instructional Videos. Issue 6 (25th June 2021) - Levin, Daniel T.; Salas, Jorge A.; Wright, Anna M.; Seiffert, Adrianne E.; Carter, Kelly E.; Little, Joshua W.
Abstract: Although eye tracking has been used extensively to assess cognitions for static stimuli, recent research suggests that the link between gaze and cognition may be more tenuous for dynamic stimuli such as videos. Part of the difficulty in convincingly linking gaze with cognition is that in dynamic stimuli, gaze position is strongly influenced by exogenous cues such as object motion. However, tests of the gaze‐cognition link in dynamic stimuli have been done on only a limited range of stimuli often characterized by highly organized motion. Also, analyses of cognitive contrasts between participants have been mostly been limited to categorical contrasts among small numbers of participants that may have limited the power to observe more subtle influences. We, therefore, tested for cognitive influences on gaze for screen‐captured instructional videos, the contents of which participants were tested on. Between‐participant scanpath similarity predicted between‐participant similarity in responses on test questions, but with imperfect consistency across videos. We also observed that basic gaze parameters and measures of attention to centers of interest only inconsistently predicted learning, and that correlations between gaze and centers of interest defined by other‐participant gaze and cursor movement did not predict learning. It, therefore, appears that the search for eye movement indices of cognition during dynamic naturalistic stimuli may be fruitful, but we also agree that the tyranny of dynamic stimuli is real, and that links between eye movements and cognition are highly dependent on task and stimulus properties.